2016
DOI: 10.1002/nme.5432
|View full text |Cite
|
Sign up to set email alerts
|

Higher‐order multi‐resolution topology optimization using the finite cell method

Abstract: SUMMARYThis article presents a detailed study on the potential and limitations of performing higher-order multiresolution topology optimization with the finite cell method. To circumvent stiffness overestimation in high-contrast topologies, a length-scale is applied on the solution using filter methods. The relations between stiffness overestimation, the analysis system, and the applied length-scale are examined, while a highresolution topology is maintained. The computational cost associated with nested topol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 49 publications
(58 reference statements)
3
76
1
Order By: Relevance
“…If not, different designs may show similar performance, resulting in non-unique optima and unexpected convergence behavior. Numerical results related to a similar aspect have been reported in [10], where it is shown that varying the density resolution beyond a certain threshold can lead to unacceptable solutions. Moreover, introducing more design freedom than can be observed from the model only adds to the computational burden.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…If not, different designs may show similar performance, resulting in non-unique optima and unexpected convergence behavior. Numerical results related to a similar aspect have been reported in [10], where it is shown that varying the density resolution beyond a certain threshold can lead to unacceptable solutions. Moreover, introducing more design freedom than can be observed from the model only adds to the computational burden.…”
Section: Introductionsupporting
confidence: 59%
“…The approach of increasing the polynomial interpolation order to represent more complex material descriptions is also found in the finite cell method. For more numerical examples on finite cell method-based TO that illustrate the interplay between design and analysis resolutions, see [10]. From the numerical cases studied earlier, it can be understood that the proper choice of the number of design points depends on the chosen FEM scheme.…”
Section: Numerical Examplementioning
confidence: 99%
“…On the other hand, there are some studies that choose to increase the resolution of the design variable mesh and maintain a coarser finite element mesh. Based on the work of Nguyen (2010), the high-order finite elements were used to improve the accuracy and efficiency of the algorithm (Groen et al 2017). An adaptive refinement/coarsening criterion was used to further accelerate the multi-resolution topology optimization method (Gupta et al 2018).…”
Section: Method Moving Morphablementioning
confidence: 99%
“…Immersed finite element techniques, such as the finite cell method [1][2][3], Cut-FEM [4,5] and immersogeometric analysis [6,7], have been successfully applied to a broad range of problems. Noteworthy applications include isogeometric analysis on trimmed CAD objects, e.g., [8][9][10][11][12][13], fluid-structure interaction with large displacements, e.g., [14][15][16][17][18][19][20][21], scan based analysis [22][23][24][25][26][27] and topology optimization, e.g., [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%